2022
DOI: 10.23960/jpmipa/v23i3.pp1286-1295
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Argumentation Skills and Problem Based Learning on Science Literacy of High School Students

Abstract: Argumentation is one of the methods used to strengthen students' scientific concepts, especially in biology learning. This quantitative study aims to determine the effect of argumentation skills on students' scientific literacy and also to find out the improvement of students' scientific literacy by using argumentation skills of class X IPA-1 MAS CIPTA students of Simpang Dolok village. The population in this study involved the entire class X IPA-1 MAS CIPTA Simpang Dolok village, the sampling in this study us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Fadlika et al, (2022) The results of the study concluded that there was a correlation between argumentation abilities and students' scientific literacy, with a correlation coefficient of 0.426 in the moderate category. Mawaddah & Khairuna, (2022) This study's results indicate a positive and significant linear effect between argumentation skills and students' scientific literacy and a significant increase in students' scientific literacy using argumentation skills. Chin et al (2016).…”
Section: Novitasariet Al (2022)mentioning
confidence: 65%
See 1 more Smart Citation
“…Fadlika et al, (2022) The results of the study concluded that there was a correlation between argumentation abilities and students' scientific literacy, with a correlation coefficient of 0.426 in the moderate category. Mawaddah & Khairuna, (2022) This study's results indicate a positive and significant linear effect between argumentation skills and students' scientific literacy and a significant increase in students' scientific literacy using argumentation skills. Chin et al (2016).…”
Section: Novitasariet Al (2022)mentioning
confidence: 65%
“…In line with Nurhusna et al (2018), students tend to be firm, intense, assertive, active, and confident in learning in identifying tasks, collecting data, and producing arguments. Based on the analysis of the six articles in Table 2 in the result, it is known that argumentation skills are effective in improving students' scientific literacy abilities (Chin et al, 2016;Delfita et al, 2021;Fadlika et al, 2022;Mawaddah & Khairuna, 2022;Sengul, 2019). Farida & Gusniarti (2015) define scientific argumentation as a human skill in compiling an opinion supported by evidence and real reasons and aims to defend an opinion.…”
Section: Discussionmentioning
confidence: 99%
“…The learning environment that is integrated with technology and implemented through STEM has an impact on increasing the professional competence of teachers in fiber learning increasing the use of digital so that it has a positive impact on the field of teaching and learning (DeCoito & Estaiteyeh, 2022). STEM implementation in learning can be used to develop the potential of both general and blind students (Indriani & Yuli, 2022) through direct or indirect learning or through the development of teaching materials such as STEM-based LKPD to direct learning so that it can provide student learning experiences, stimulate, develop students' science process skills (Febriyanti & Maryani, 2020;Makalunsenge, Yusuf, & Lamangantjo, 2022) and skilled in improving critical thinking skills and scientific literacy through digital literacy which is ultimately able to be skilled in solving problems in real life (F. Handayani, 2020;M. Handayani & Khairuna, 2022;Siti Maisarah, Miriam, Mahtari, & Suyidno, 2022).…”
Section: Descriptive Analysis Resultsmentioning
confidence: 99%
“…Metode ini mengacu pada cara guru atau instruktur menunjukkan suatu kegiatan atau proses kepada siswa atau peserta didik secara langsung, dengan tujuan agar peserta didik dapat memahami, mengamati, dan mengikuti cara melakukan kegiatan atau proses tersebut dengan benar. (Handayani, D., Fauzi, A., & Puspitaningrum, 2021) Sehingga hal yang disaksikan oleh anak didik di contoh yang menyebabkan lebih mudah memahami mata pelajaran.…”
Section: Demonstrasiunclassified